2003
DOI: 10.1021/bi026639s
|View full text |Cite
|
Sign up to set email alerts
|

Binding of 2-Aryl-4-(piperidin-1-yl)butanamines and 1,3,4-Trisubstituted Pyrrolidines to Human CCR5:  A Molecular Modeling-Guided Mutagenesis Study of the Binding Pocket

Abstract: The results of investigations in these laboratories of 2-aryl-4-(piperidin-1-yl)butanamines and 1,3,4-trisubstituted pyrrolidines as human CCR5 antagonists have recently been disclosed. To facilitate further development of these antagonists, we have developed a pharmacophore model based on the structure-activity relationships (SAR) and a human CCR5 receptor docking model using the crystal structure of rhodopsin as a template [Palczewski, K., et al. (2000) Science 289, 739-745]. Guided by the receptor docking m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
63
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 24 publications
11
63
0
1
Order By: Relevance
“…The left side of LMD-009 is suggested to be in close proximity to and dependent upon TyrIII:08 in the major binding pocket as described for almost all characterized CC-chemokine receptor antagonists (Berkhout et al, 2003;Castonguay et al, 2003;de Mendonça et al, 2005;Maeda et al, 2006;Vaidehi et al, 2006) and position III:08-in the form of an Asp-is also a key-interaction point for the monoamines . The orientation of LMD-009 was mainly provided by studying the four analogs, LMD-584, LMD-902, LMD-268, and LMD-174, with variation in the left side compared with LMD-009, because they all reacted very differently from LMD-009 to mutations in the major binding pocket.…”
Section: Nonpeptide Agonist and Antagonists Interact With Gluvii:06 337mentioning
confidence: 83%
See 3 more Smart Citations
“…The left side of LMD-009 is suggested to be in close proximity to and dependent upon TyrIII:08 in the major binding pocket as described for almost all characterized CC-chemokine receptor antagonists (Berkhout et al, 2003;Castonguay et al, 2003;de Mendonça et al, 2005;Maeda et al, 2006;Vaidehi et al, 2006) and position III:08-in the form of an Asp-is also a key-interaction point for the monoamines . The orientation of LMD-009 was mainly provided by studying the four analogs, LMD-584, LMD-902, LMD-268, and LMD-174, with variation in the left side compared with LMD-009, because they all reacted very differently from LMD-009 to mutations in the major binding pocket.…”
Section: Nonpeptide Agonist and Antagonists Interact With Gluvii:06 337mentioning
confidence: 83%
“…Nonpeptide antagonists against CC-chemokine receptors usually share a common pharmacophore with a rather centrally located, positively charged amine Seibert et al, 2006). This amine has been shown to interact with a highly conserved Glu in the extracellular end of TM-VII (in position VII:06), whereas the flanking groups have been shown to interact with conserved aromatic residues, as well as other residues specific for each chemokine receptor (Mirzadegan et al, 2000;Castonguay et al, 2003;Tsamis et al, 2003;de Mendonça et al, 2005;Maeda et al, 2006;Seibert et al, 2006). Thus, all CC-chemokine receptor nonpeptide antagonists with characterized binding modes interact with GluVII:06 [except for the recently characterized binding pocket of BX471 in CCR1 (Vaidehi et al, 2006)] in addition to aromatic residues in the major binding pocket (composed of TM-III, TM-IV, TM-V, TM-VI, and TM-VII) and in the minor binding pocket (composed of TM-I, TM-II, TM-III, and TM-VII) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of a high-resolution structure of a gp120-coreceptor complex, biochemical studies of CCR5 have revealed the importance of its Nterminus (Nt) and second extracellular loop (ECL2) in binding gp120 and mediating viral entry (reviewed in [34]). Small molecule CCR5 inhibitors, on the other hand, are believed to bind within a cavity between the transmembrane (TM) helices on the extracellular surface of the coreceptor, as suggested by site-directed mutagenesis experiments and molecular modeling of CCR5 on the basis of the available crystal structure of bovine rhodopsin that is characterized by a similar TM topology [100,101]. More specifically, the binding "pocket" of such molecules as TAK-779, AD101, and SCH-C is thought to be located between TM helices 1-3, and 7; other TM helices, particularly helix 6, contribute to some compound-specific variations [102,103].…”
Section: Small Molecule Ccr5 Inhibitorsmentioning
confidence: 99%